Nanotechnology for Pediatric Retinoblastoma Therapy - Eleonora Russo; Andrea Spallarossa; Bruno Tasso; Carla Villa; Chiara Brullo (MDPI AG, 2022)
Retinoblastoma is a rare, sometimes hereditary, pediatric cancer. In high-income countries this disease has a survival rate approaching 100%, while in low- and middle-income countries the prognosis is fatal for about 80% of cases. Depending on the stage of the disease, different therapeutic protocols are applied. In more advanced forms of the disease, surgical removal of the entire globe and its intraocular contents (enucleation) is, unfortunately, necessary, whereas in other cases, conventional chemotherapy is normally used. To overcome the side-effects and reduced efficacy of traditional chemotherapic drugs, nanodelivery systems that ensure a sustained drug release and manage to reach the target site have more recently been developed. This review takes into account the current use and advances of nanomedicine in the treatment of retinoblastoma and discusses nanoparticulate formulations that contain conventional drugs and natural products. In addition, future developments in retinoblastoma treatment are discussed.